Sources of Energy, Empty Calories, Added Sugars, and Solid Fats Among Children and Adolescents 2–18 Years in the United States. (29th May 2020) - Wambogo, Edwina; Reedy, Jill; Shams-White, Marissa; Herrick, Kirsten; Lerman, Jennifer; O'Connor, Lauren
Abstract: Objectives: To identify top dietary sources of energy, empty calories, added sugars, and solid fats among 2–18 year old children and adolescents in the U.S. and describe trends. Methods: Day 1 24-hour dietary recalls from the NHANES Survey were categorized according to the What We Eat in America Food categories and used to examine food sources (percentage contribution and mean intake) of total energy and energy from added sugars and solid fats (collectively, empty calories). Trends over time between 2007–2016 were examined in 2–18-year-olds. Significance was set at P  < 0.05. Results: The top five sources of energy overall from 2007–2016 for 2–18-year-olds were pizza (5.8%), other sandwiches (3.9%), soft drinks (3.4%), cakes and brownies (3.1%), and flavored milk (2.6%). Energy intake decreased between 2007–08 to 2015–16, largest decrease between 2011–12 to 2015–16 for 2–3-year-olds (–8.7%, P  = 0.02) and for 4–8-year-olds (–6.8%, P  = 0.0005); and from 2009–10 to 2015–16 for 14–18-year-olds (–7.0%, P  = 0.005). In all age groups, empty calories declined, regardless of energy intake. Nevertheless, in all age groups, >25% of total energy intake came from empty calories: 2–3-year-olds (26.1%–30.0%), 4–8-year-olds (30.0%–33.6%), 9–13-year-olds (30.2%–34.4%), and 14–18-year-olds (30.5%–35.5%). Over time the top sources of energy and empty calories did not vary greatly within each age group, but with increasing age, there was a shift from beverages to solid foods, and in types of beverages. For example, of the top five energy sources among 2–3 year-olds, four were beverages (flavored milk, 3.9–5.7%; whole milk, 3.4–5.4%; reduced fat milk, 4.2–5.3%, and fruit drinks, 2.9–3.1%), among 4–8 year-olds, two were beverages (flavored milk, 3.2–4.7% and fruit drinks, 3.1–3.3%), and among 9–13 year-olds and 14–18 year-olds, mainly soft drinks (3.4–4.7% and 4.1–6.3%, respectively), and in some years, fruit drinks (2.7% and 2.9%, respectively). Conclusions: There is an overlap in top sources of energy and empty calories: flavored milk, fruit drinks, whole milk, reduced fat milk, soft drinks, pizza, cookies and brownies, and other sandwiches. Continued research on how the sources of empty calories transition from early childhood into adolescence can inform how to modify the food landscape to include fewer empty calorie foods and potentially address excess energy intake. Funding Sources: N/A.